East and West, North and South - Jones, A. M. (International Library of African Music, 1954)
“East and West, North and South, ’Frisco to Perim. . . “ So we used to sing in a drawing-room ballad whose context certainly had nothing to do with African music. Yet the universality suggested by the points of the compass has a bearing on that music, which becomes ever more cogent as research penetrates more and more of the great continent.
Keywords: Ethnomusicology; Music; Africa; West Africa; East Africa; Sub-Saharan Africa; Foreign Influences; African Music; Musical Meter; Musical Rhythm